2012
DOI: 10.1073/pnas.1119569109
|View full text |Cite
|
Sign up to set email alerts
|

Salience driven value integration explains decision biases and preference reversal

Abstract: Human choice behavior exhibits many paradoxical and challenging patterns. Traditional explanations focus on how values are represented, but little is known about how values are integrated. Here we outline a psychophysical task for value integration that can be used as a window on high-level, multiattribute decisions. Participants choose between alternative rapidly presented streams of numerical values. By controlling the temporal distribution of the values, we demonstrate that this process underlies many puzzl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
276
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(323 citation statements)
references
References 32 publications
42
276
5
Order By: Relevance
“…increased risk taking. These results differ from the common observation of risk aversion in the gain domain (e.g., Kahneman & Tversky, 1979) and are consistent with recent studies that demonstrated that feedback can lead to risk seeking in the gain domain (Ludvig & Spetch, 2011;Tsetsos, Chater, & Usher, 2012 x2, p2; …; y) refers to a prospect that yields a payoff of x1 with probability p1, a payoff of x2 with probability p2, …, and y otherwise. Proportions of the riskier choice are shown in five blocks of five trials each (Block 1:…”
Section: Full Information Problems Analysis Of the 46 Full Informatisupporting
confidence: 78%
“…increased risk taking. These results differ from the common observation of risk aversion in the gain domain (e.g., Kahneman & Tversky, 1979) and are consistent with recent studies that demonstrated that feedback can lead to risk seeking in the gain domain (Ludvig & Spetch, 2011;Tsetsos, Chater, & Usher, 2012 x2, p2; …; y) refers to a prospect that yields a payoff of x1 with probability p1, a payoff of x2 with probability p2, …, and y otherwise. Proportions of the riskier choice are shown in five blocks of five trials each (Block 1:…”
Section: Full Information Problems Analysis Of the 46 Full Informatisupporting
confidence: 78%
“…Email: k.tsetsos62@gmail.com. Previously, we showed that, when a third (decoy) alternative (D) alters the ranking of two existing alternatives, A and B, the model successfully predicts a preference reversal, despite the fact that the attribute values of A and B remain intact (Table S1) (14). In the current report, we show that selective integration also explains intransitive choice behavior in humans.…”
Section: Significancesupporting
confidence: 48%
“…Here, we describe an alternative theory, known as "selective integration" (14), that overcomes this challenge by offering a normative justification of choice irrationality. Building on psychophysical research into the neural and computational mechanisms by which decisions are formed via sequential sampling (15), we assume that choice attributes (e.g., the expense, weather, or culture encountered on holiday) are sampled in turn (2), and integrated toward a cumulative decision variable (16).…”
mentioning
confidence: 99%
“…Some recent studies of decisions from experience have observed risk seeking for gains (e.g., Ludvig, Madan, Pisklak, et al, 2014;Tsetsos et al, 2012;Zeigenfuse et al, 2014), even though the bulk of studies does not (e.g., Erev, Glozman, & Hertwig, 2008;Erev et al, 2010). Though the experimental procedures used in these studies differ on a variety of dimensions (e.g., number of outcomes and presence of extreme values), the two studies that involved some time pressure observed risk seeking for gains (Tsetsos et al, 2012;Zeigenfuse et al, 2014), though not for losses. The current results further suggest that time pressure may indeed be an important contributor to these differences in risky-choice behaviour in the gain domain.…”
Section: Discussionmentioning
confidence: 94%
“…One manipulation that can induce risk seeking involves priming memories for past winning outcomes (Ludvig, Madan, & Spetch, 2015). A second manipulation involves altering the decision context: risky options that lead to the best possible outcome in a context are more likely to be chosen, a pattern termed the extreme-outcome rule (Ludvig, Madan, Pisklak, & Spetch, 2014b;; see also Tsetsos, Chater, & Usher, 2012;Zeigenfuse, Pleskac, & Liu, 2014). In this paper, we evaluate whether time pressure, known to increase risk seeking in decisions from description, is a third manipulation that would increase risk seeking in decisions from experience.…”
Section: Introductionmentioning
confidence: 99%